Sistem Informasi Layanan Home Care Berbasis Web Pada Praktek Perawatan Mandiri Ishak Holistic Kabupaten Bantaeng - Jumrah Jumrah; Raden Wirawan; Sri Asfirawati Halik (Institut Teknologi dan Bisnis Bina Adinata, 2024)
This study aims to: (1) design a Web-Based Home Care Service Information System at Ishak Holistic Self-Care Practice, Bantaeng Regency. (2) how is the user response to the web-based home care service information system at Ishak Holistic Independent Care Practice Bantaeng. This research uses the waterfall method. This method uses 6 stages, namely Analysis, Design, Coding, Testing, Implementation, Maintenance. In this study using UML (Unifed Modeling Language) design, namely Use Case Diagram, Class Diagram, Activity Diagram and Sequence Diagram. This research produces a web-based home care service information system at the Ishak Holistic Independent Care Practice of Bantaeng Regency which can be used on computers and android smartphones. This research uses instruments in the form of questionnaires to determine user responses, namely officers of the Ishak Holistic Independent Care Practice of Bantaeng Regency and the people of Bantaeng, Pa'jukukang District. Based on the response of the Independent Care Practice officers where the system as a whole is interesting with the completeness of its features in accordance with what is needed so that it encourages the public to use it because the system can be accessed easily and can be read and understood by the community. The value obtained from the results of data analysis is 90% with a very suitable category. While the community's response, this system is easy to use, not complicated and in accordance with the needs of the community so that it helps the community in getting health services at home, consulting through the website, knowing the stock of available drugs without having to come to the Independent Care Practice where the is easily accessible anywhere using a cellphone or laptop. The value obtained is 92% with a very suitable category.